Gestational age at birth and outcome in monochorionic twins with different types of selective fetal growth restriction: A systematic literature review. (17th July 2022) - el Emrani, Salma; Groene, Sophie G.; Verweij, E. Joanne; Slaghekke, Femke; Khalil, Asma; van Klink, Jeanine M. M.; Tiblad, Eleonor; Lewi, Liesbeth; Lopriore, Enrico
Abstract: This systematic review aims to assess the gestational age at birth and perinatal outcome [intrauterine demise (IUD), neonatal mortality and severe cerebral injury] in monochorionic twins with selective fetal growth restriction (sFGR), according to Gratacós classification based on umbilical artery Doppler flow patterns in the smaller twin. Seventeen articles were included. Gestational age at birth varied from 33.0 to 36.0 weeks in type I, 27.6–32.4 weeks in type II, and 28.3–33.8 weeks in type III. IUD rate differed from 0%–4% in type I to 0%–40% in type II and 0%–23% in type III. Neonatal mortality rate was between 0%–10% in type I, 0%–38% in type II, and 0%–17% in type III. Cerebral injury was present in 0%–2% of type I, 2%–30% of type II and 0%–33% of type III cases. The timing of delivery in sFGR varied substantially among studies, particularly in type II and III. The quality of evidence was moderate due to heterogenous study populations with varying definitions of sFGR and perinatal outcome parameters, as well as a lack of consensus on the use of the Gratacós classification, leading to substantial incomparability. Our review identifies the urgent need for uniform antenatal diagnostic criteria and definitions of outcome parameters. Key points: What is already known about this topic? Selective fetal growth restriction (sFGR) with abnormal umbilical artery Doppler flow patterns in the smaller twin (type II and III) is associated with poor perinatal outcome. International consensus on optimal antenatal and perinatal management is lacking. Whether timing of delivery and gestational age (GA) at birth varies between international centers is not well known. What does the study add? GA at birth in sFGR twins varies substantially between international centers, especially in type II and III: type I = 33.0–36.0 weeks, type II = 27.6–32.4 weeks and type III = 28.3–33.8 weeks. Fetal and neonatal mortality rates were highest in type II and type III. Cerebral injury was present in 2%–30% in type II and 0%–33% in type III cases. Our review identifies the urgent need for uniform antenatal diagnostic criteria, definitions of outcome parameters and standardized long‐term follow‐up in sFGR.